2005
DOI: 10.1097/01.mnm.0000171785.03403.6f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation therapy on oesophageal transit in patients with inner quadrant breast tumour

Abstract: Oesophageal transit seems to be affected by radiation even without a clinically significant oesophageal symptom and oesophageal scintigraphy allows sensitive, non-invasive and quantifiable assessment of the oesophageal transit time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Esophageal motility was evaluated before and immediately after RT using esophageal scintigraphy. Post-irradiation therapy ETT values were significicantly higher compared to pre-radiation therapy ETT values (p<0.001) (Turkolmez et al, 2005). These results confirm the results of our study.…”
Section: 53 Oral Glutamine Supplementation For Esophagitis In Lung Csupporting
confidence: 82%
See 1 more Smart Citation
“…Esophageal motility was evaluated before and immediately after RT using esophageal scintigraphy. Post-irradiation therapy ETT values were significicantly higher compared to pre-radiation therapy ETT values (p<0.001) (Turkolmez et al, 2005). These results confirm the results of our study.…”
Section: 53 Oral Glutamine Supplementation For Esophagitis In Lung Csupporting
confidence: 82%
“…The presence of these symptoms, which are clinical manifestations of dyskinesia and mucositis respectively, suggests that radiation induced acute esophagitis might be associated with altered organ motillity (Sasso et al, 2008). A variety of studies have shown that irradiation of the esophagus causes early mucosal changes and acute effects on esophageal motility or transit (Turkolmez et al, 2005;Sasso et al, 2008). Clinical and dosimetric factors may be related to the incidence and severity of acute radiation esophagitis.…”
Section: Introductionmentioning
confidence: 99%
“…Acute radiation esophagitis often lead to dysphagia and odynophagia due to mucosal changes and effects on esophageal motility . [18,19] ARIE was not only related to body weight loss, poor nutrition, and poor quality of life but also decreased the effective treatment dose of radiotherapy, increased unplanned treatment course delay, causing decreased tumor control and survival rate . [20] Late radiation-induced esophagitis usually refer to onset more than 3 months after the completion of thoracic irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…23 Radiotherapy increases the ETT in 80% of patients, even at low doses. 21,24 No data are available on the ETT at higher doses or with CCRT, but most likely the severity and incidence of increased ETT will be higher. It is unknown when and if the esophageal motility returns to normal after CCRT.…”
Section: Smoking Cessationmentioning
confidence: 99%